Effectiveness of Moviprep® as colonic preparation - cleansing right colon for Lynch Syndrome (LS) screening: a prospective study - De Villiers, David Johannes (Department of Surgery, 2017)
Purpose: Each year, a cohort in the Northern Cape undergo colonoscopies as part of a surveillance program for individuals who have a C1528T mutation in the hMLH1 gene that puts them at very high risk for the development of colon cancer (Lynch syndrome). A clean colon is essential as it allows a thorough evaluation and surveillance for small polyps or mucosal lesions mostly encountered in the ascending colon. This study evaluated both the subject acceptance and the effectiveness of a 2L PEG electrolyte lavage solution containing ascorbic acid and sodium ascorbate (Moviprep®) as a preparation solution. Methods: The screening program was divided into two stages. Stage 1, 71 subjects were counselled individually on the importance of bowel cleansing and the use of Moviprep® as their bowel cleansing agent. Preparation was either a) 2L the night prior to colonoscopy or b) 1L the night prior to and the second litre on the morning of the colonoscopy. Subjects were encouraged to drink at least 500ml clear fluid in addition to each litre of Moviprep®. Informed consent was obtained for participation in the study. Stage 2, approximately 6 weeks later, each subject completed a questionnaire, evaluating their experience with Moviprep® and also had their screening colonoscopy performed. Colonoscopies were performed at 4 medical facilities in the Northern Cape. All subjects were assessed for bowel cleanliness on arrival at the facility where colonoscopy was to be performed. If any of the subjects were found to be inadequately cleaned, extra oral preparation was given prior to colonoscopy. The Harefield cleansing scale was used to evaluate the quality of colonic cleansing during each colonoscopy. The colon was divided into 6 segments (rectum, sigmoid, descending-, transverse-, ascending colon and cecum). Preparation was scored as A = all colon segments clean; B = at least 1 segment with residual amounts of brown liquid or semisolid stool, which can easily be displaced or removed; C = at least 1 segment with only partially removable stool, preventing complete visualization; D = at least 1 segment which could not be examined due to solid stool). Grades A or B were considered successful cleansing and grades C or D were considered a failed colonic preparation. Results: A total of 46 subjects had colonoscopies performed. 41(89%) of them had successful and 5(11%) failed preparation. Three of those subjects that prepared successfully had previously undergone right hemicolectomies, leaving 38 with intact colons. 22/38 (58%) subjects achieved an A grade for caecal cleansing and 16/38 (42%) a B grading. 2438 (63%) subjects scored an A grade for the ascending colon and 14/38 (37%) a B grade. A total of 64 subjects completed the questionnaires of which 83% (53/64) had used other colon preparations previously. When asked if they would use Moviprep® again in the future, 89% (57/64) said yes and 11% (7/64) said no. 94% of subjects (60/64) would recommend Moviprep® to friend and family. Conclusion: Moviprep® provided adequate colonic cleansing in 89% of subjects. In addition, nearly 90% of subjects were satisfied with the product and would use it again.